TULANG NAPIER DAN GEOBOARD: EDUKASI DAN PELATIHAN ALAT PERAGA MATEMATIKA BAGI SISWA SEKOLAH DASAR - Purwasih, Ratni; Rifa’i, Rusdian; Nasrullah, Anton; Nurjanah, Nurjanah (Jurnal Pengabdian Masyarakat Khatulistiwa, 2022)
ABSTRACTThis community service aims to improve the multiplication operation ability of the students of SD Melong Mandiri 5 on mathematics material through education of nafier bone and geoboard mathematics learning media. The subjects of this service activity are 3rd grade students of SD Melong Mandiri 5 Cimahi. The stages of service activities include the observation stage, the planning and preparation stage, the implementation stage and the evaluation stage. The observation phase focuses on finding the partner's priority problems. The planning stage consists of determining the schedule of service, licensing, training subject classes, providing teaching aids and discussing appropriate solutions with partners. The implementation phase includes education and training of mathematics teaching aids to improve multiplication operation skills and recognition of flat shapes. The evaluation stage is carried out by analyzing the results of student work and the student presentation process. The method applied is the provision of material regarding multiplication and geometry as well as drill and practice. The place of implementation is at SD Melong Mandiri 5, Cimahi City. The number of participants is 37 3rd grade elementary school students. The results of this service activity consist of: (1) the use of the nafier bone for multiplication makes it easier for students to learn; (2) students understand and recognize various kinds of flat shapes; (3) improve students' understanding abilities to the multiplication operation.Keywords: Geobord, Nafier Bone ,Props ABSTRAKPengabdian kepada masyarakat ini bertujuan untuk meningkatkan kemampuan operasi perkalian  siswa SD Melong mandiri 5 pada materi matematika melalui edukasi media pembelajaran matematika tulang nafier dan geoboard. Subjek  kegiatan pengabdian ini yaitu  siswa kelas 3 SD Melong mandiri 5  Cimahi. Tahapan kegiatan pengabdian meliputi tahap observasi, tahap perencanaan dan persiapan, tahap pelaksanaan dan tahap evaluasi. Tahap observasi berfokus pada mencari masalah prioritas pihak mitra. Tahap perencanaan terdiri dari kegiatan penentuan jadwal pengabdian, perizinan, kelas subjek pelatihan, penyedian alat peraga dan diskusi solusi yang sesuai dengan mitra. Tahap pelaksanaan meliputi edukasi dan pelatihan alat peraga matematika untuk meningkatkan kemampuan operasi perkalian dan pengenalan bentuk bangun datar. Tahapan evaluasi dilakukan dengan cara menganalisis hasil pekerjaan siswa dan proses presentasi siswa. Metode yang diterapkan adalah pemberian materi berkenaan perkalian dan geometri serta drill dan  praktek. Tempat pelaksanaan di SD Melong Mandiri 5 Kota Cimahi. Jumlah peserta adalah 37 siswa kelas 3 SD.. Hasil dari kegiatan pengabdian ini terdiri dari: (1) penggunaan tulang nafier untuk perkalian memudahkan siswa belajar;(2) siswa memahami dan mengenal macam-macam bangun datar;(3) meningkatkan kemampuan pemahamana siswa terhadap operasi perkalian.Kata Kunci: Alat Peraga, Geobord, Tulang Nafier.